Negotiating the ethical terrain in global value chains on the road towards the SDGs - Sinkovics, Noemi; Hoque, Samia Ferdous; Sinkovics, Rudolf R.; Gunaratne, Denanjalee (Palgrave Macmillan, 2025)
This paper employs a pattern matching approach to explore the tensions arising from differences in the ethical dispositions of multinational enterprise (MNE) buyers and their suppliers within the Bangladeshi apparel manufacturing sector. It examines how varying ethical principles shape the development, implementation, and outcomes of corporate social responsibility (CSR) and labor standards. Our analysis resulted in the identification of four scenarios: legitimacy with friction, mitigated forced alignment, collaborative enhancement, and principled resistance. However, the scenario, principled resistance, is purely conceptual, as none of our empirical cases aligned with this category. We extend work highlighting the importance of ethical foundations for strategic decision making. This study advances the understanding of global value chain governance, particularly regarding MNEs’ contribution to the socially oriented Sustainable Development Goals. Our findings suggest that, out of the four scenarios, the combination of virtue ethics and consequentialist principles is most likely to facilitate a just transition to a more desirable state in contexts characterized by development challenges and institutional voids.
Keywords: Strategic decision making; Normative ethics; GVC governance; CSR codes; Human rights; MNEs; Suppliers; Supply chain collaboration; Virtue ethics; Deontology; Consequentialism; Sustainable development goals (SDG); InnoLab; InnoLab